Pengaruh Pembelajaran Online Terhadap Hasil Belajar Tik Siswa Kelas XI MIPA di SMA Negeri 1 Lembah Gumanti - Anggraeni, Sari Fitria; Zakir, Supratman (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to determine the effect of online learning on ICT learning outcomes for students of class xi mipa at SMA Negeri 1 Lembah Gumanti. Respondents were 151 students of class XI MIPA with a sample of 60 students from the student population. In this study using quantitative methods with data testing using SPSS 22. Data were obtained by filling out questionnaires by students. The tests carried out are validity, reliability, and R Square to find out how much influence online learning has on students' ICT learning outcomes. The results showed that there was a significant positive effect between the influence of online learning on learning outcomes. It can be seen that the value of sig.(2-tailed) for each variable X and variable Y is < 0.005. Judging from the values of rcount and rtable, the result is that the value of rcount > rtable. Rtable value0.254. variable X has a Cronbach's alpha value > 0.06, namely variable X with a value of 0.759, thus the design of the questionnaire questions on the online learning variable is reliable. The value of R square is 0.832, which means that the independent variable (online learning) is able to explain the dependent variable (learning outcomes) of 83.2% and the rest is determined or explained by other variables not explained in thisstudy. According to the ICT teacher in class XI MIPA, student learning outcomes tend to be stable and do not experience a decline, even though learning is carried out boldly.